Dialogue - Raimond, Paul (Academy of Management Review, 1999)
The article focuses on commentary concerning the article “Negotiating with Yourself and Losing.” It states that “multiple-selves” phenomena is the ability to see situations from more than one perspective. It suggests that psychologists and researchers may find the multiple-selves phenomena annoying as it makes it more difficult to create a rational analytical model of cognition, but that this ability can help managers utilize their creativity by looking outside the box. It utilizes the example of business schools as an example of this phenomena on an organizational scale with one group seeing the school as academic in nature while another may feel it should be run more like an actual business.